Analytical and experimental study on slender concrete-filled steel tube columns and beam-columns - Perea, Tiziano (Georgia Institute of Technology, 2011)
The use of composite steel-concrete columns and beam-columns in many structural systems is increasing globally due to the intrinsic synergy when these materials are designed and detailed together properly. However, limited test data are available to justify the structural system response factors and comprehensive design equations in current design specifications. This research, through the testing of 18 full-scale, slender concrete-filled steel tube (CFT) beam-columns, attempts to address the latter need. The circular and rectangular CFT specimens tested for this research are by far the longest and the most slender full-scale CFT members tested worldwide. These CFT specimens were subjected to a complex load protocol that includes pure compression, uniaxial and biaxial bending combined with compression, pure torsion, and torsion combined with compression. In addition, data from the hydrostatic pressure on the steel tubes due to the fresh concrete at casting was evaluated. The single most important contribution of this research is the clarification of the interaction between strength and stability in slender composite concrete-filled columns and beam-columns. Parallel to the experimental study, advanced computational analyses were carried out to calibrate material and element models that characterize the salient features of the observed CFT response, such as steel local buckling and residual stresses, concrete confinement, stability effects, strength, and stiffness degradation, among others. Based on the observed behavior, simplified guidelines for the computation of the strength and stiffness parameters for CFT columns and beam-columns are proposed for design purposes.